Venetoclax in the treatment of secondary plasma cell leukemia with translocation t(11;14): a case report and literature review - Elsabah, Hesham; Ghasoub, Rola; El Omri, Halima; Benkhadra, Maria; Cherif, Honar; Taha, Ruba Y. (Frontiers in Oncology, 2024)
Introduction: Venetoclax is a BCL2 inhibitor with proven efficacy in patients with multiple myeloma (MM) and translocation (t) 11;14. However, its role in plasma cell leukemia (PCL) remains unclear. Herein, we aimed to report a case of relapsed MM with secondary PCL and t(11;14) achieving complete (CR) and durable remission with venetoclax therapy. Case presentation: A 52-year-old gentleman was diagnosed with MM-free light chain lambda (ISS III)in December 2016. He received induction therapy, followed by Autologous Stem Cell Transplant (ASCT) in May 2017 and maintenance. A year later, the patient relapsed with secondary PCL. His cytogenetics analysis revealed translocation t(11; 14). The patient failed salvage chemotherapy and was shifted to venetoclax with dexamethasone treatment. The patient attained complete remission CR, which was maintained for 2 years and a half before he developed fatal COVID-19 pneumonia. Conclusion: In comparison with the reported literature, this case report offers the latest compilation of the available evidence on the use of venetoclax in patients with PCL. Furthermore, our patient achieved CR for the longest reported durable response in literature thus far. Prospective clinical trials are needed to elucidate the optimal dosage, combination, and duration of treatment, ensuring better representation and generalizability of the findings.Meanwhile, venetoclax may be considered as a therapeutic option in patients with PCL t(11;14).